Cardio-Metabolic Health Venezuelan Study (EVESCAM): Design and Implementation. - Nieto-Martínez, Ramfis; Marulanda, María Inés; González-Rivas, Juan P.; Ugel, Eunice; Durán, Maritza; Barengo, Noel; Aschner, Pablo; Patiño, Mario; López Gómez, Luis; Monsalve, Pedro; Marcano, Héctor; Florez, Hermes (Investigación Clínica, 2017)
The EVESCAM (EstudioVenezolano de Salud Cardio-Metabólica) is the first national, population survey in Venezuela, designed to examine the prevalence of diabetes and cardio-metabolic risk factors and its relationship with lifestyle. It is a cross-sectional, cluster sampling study, which recruited 4454 participants aged â‰¥20 years. The data were collected in community health-care centers by trained health professionals and medical students. The data collected from each subject included, after informed consent, structured questionnaires (clinical, demographic, physical activity, nutritional and psychological), anthropometric measurements (weight, height and waist circumference), body fat by bioelectrical impedance, hand grip, blood pressure, electrocardiogram, and biochemical measurements (standard 75 g oral glucose tolerance test, total cholesterol, HDL-cholesterol, LDL-cholesterol and triglycerides). The data will be used to estimate the prevalence of overweight, obesity, prediabetes, diabetes, hypertension, dyslipidemias, sarcopenia and metabolic syndrome; and to examine their relationships with lifestyle factors. The risk of coronary heart disease and impaired glucose regulation will be estimated using the Framingham Coronary Heart Disease Risk Score and the Latin America adaptation of the Finnish Diabetes Risk Score (LA-FINDRISC), respectively. These results will guide national cardiovascular and diabetes prevention strategies, and will be available for government agencies to help in the implementation of public health policies.